The raising of the shield - Ludowyk, frederick, 1934-2012. (Canberra, [Australian Capital Territory] : Valar Publishing, 2017)
The Raising of the Shield, takes place in the Second Plane, which is peopled not only by humans but also by Wizards, Witches, Elves, Dwarves, Goblins, Trolls, and Unicorns. The Citadel of the Wizards eventually falls to the forces of Hrefn, and Rick and the Quest Companions begin their journey towards Lífmorth, the mountain on which exists the shifting castle of the gods Hrefn and Léoht.
"A trilogy"--Title page.
A novel.
Keywords: Castles -- Fiction; Witches -- Fiction; Fantasy fiction, Australian; Australian